Pharmacotherapeutic advances with anaplastic lymphoma kinase inhibitors for the treatment of non-small cell lung cancer. (23rd May 2020) - Indini, Alice; Rijavec, Erika; Ghidini, Michele; Bareggi, Claudia; Gambini, Donatella; Galassi, Barbara; Antonelli, Paola; Bettio, Giulia; Di Nubila, Clarissa; Grossi, Francesco
ABSTRACT: Introduction: Anaplastic lymphoma kinase (ALK) inhibitors are potent oral anti-cancer agents acting as tyrosine kinase inhibitors (TKIs), which are approved for the treatment of ALK+ non-small cell lung cancer (NSCLC). Over the last years, several new molecules have been developed and are currently under clinical investigation. Areas covered: In this paper, the authors review the most relevant clinical findings of ALK inhibitors in the treatment of ALK+ NSCLC. The authors discuss differences in the efficacy and treatment-related adverse events (AEs) incidence of distinct ALK inhibitors, molecular mechanisms of acquired resistance, and ongoing clinical studies assessing the use of ALK inhibitors in innovative settings and novel combinations. Expert commentary: ALK inhibitors have dramatically improved the prognosis of patients with ALK+ NSCLC and revolutionized therapy options. Nowadays, several molecules are approved for the treatment of ALK+ NSCLC, either in first or further lines of systemic treatment. Several clinical trials are currently ongoing in order to define a potential role of ALK inhibitors in combination with novel anti-cancer agents, as well as monotherapy in neo- and adjuvant settings.